Decentralized Planning, Budgeting and Service Delivery in Local Governments. A Case Study of Health and Education Services in Musanze District, Rwanda. - Samson, Maniragaba (Kabale University, 2020)
Access to quality Health and Education services is critical to socioeconomic welfare and advancement of rural areas. The motivation for this study was to investigate key factors related to health and education services delivery particularly in relation to local government planning and budgeting for effective management local government revenues and expenditure on these services. The study was based on the following objectives: to examine the impact of decentralized planning, budgeting on health and education services delivery, to analyze the relationship between participatory planning, budgeting and delivery of health and education services; to assess the challenges encountered in decentralized planning, budgeting for effective health and education service delivery; to analyze strategies of improving decentralized planning, budgeting for effective delivery of health and education services. The research methodology employed a descriptive research design. The study was based on positivism orientation since it was not purely quantitative based, with a need of qualitative data. The target population of the study consists of 628 respondents. A sample was taken from each category using the Solvein’s formula to arrive at the minimum sample size of 244. The sampling methods used included purposive and simple random sampling. Both qualitative and quantitative data was collected using interview guide and questionnaire respectively. Thus, the overall results determined by percentage for the level of effective decentralized planning and budgeting in terms of effective financial planning and budgeting, fiscal accountability and transparency has effect on delivery of health and education services delivery in Musanze district was (77.9%). The major results further indicates that, there was a significant relationship between the decentralized planning and budgeting and delivery of health and education services which was very satisfactory (76.8%). The recommendations were that the central government of Rwanda fund adequately and timely monitor the utilization of funds by local governments. Districts should improve on effective planning, budgeting in order to improve on social economic welfare of the people.